Szkic do teologii ludzkiej płciowości - Sławomir Kunka (Polonia Sacra)
Masculinity and femininity are only different sides of the same human nature. Therefore, every woman and every man enjoy the same and equally nonvolatile and absolute dignity of the human person. Masculinity and femininity serve each other in achieving their common humanity. Equality and complementarity of men and women have their basis in their common human nature, which has its reference to the Creator. Differences between men and women are associated with their different forms of carrying out their vocations: through fatherhood or motherhood, and with their different experience of suffering reaction to stimuli or shame. Gender equality, having the same human nature, and the differences between the genders generate some “tension” that can only serves the human, family and humanity.